Design Of Minimum Volume Emc Input Filters For An Ultra Compact Three-phase Pwm Rectifier - Heldwein, Marcelo L.; Kolar, Johann W. (Eletrônica de Potência, 2009)
A design procedure is proposed for the electromagnetic compatibility (EMC) filters to be included in a three-phase/-level PWM rectifier unit in order to fulfill EMC requirements related to conducted emissions. An analytical volumetric optimization is performed considering constraints given by electrical safety, power factor and damping of resonances. The procedure avoids the necessity of applying numerical optimization allowing the analytical calculation of the total filter volume as function of rated power and switching frequency. The experimental verification of the proposed procedure is presented through con- ducted emissions (CE) measurements in the designed system.